Oracle Information integration, migration, and consolidation : the definitive guide to information integration and migration in a heterogeneous world : use Oracle technologies and best practices to manage, maintain, migrate, and mobilize data /: the definitive guide to information integration and migration in a heterogeneous world : use Oracle technologies and best practices to manage, maintain, migrate, and mobilize data. (2011) - Unknown
No abstract available